2006 International Conference on Wireless Communications, Networking and Mobile Computing 2006
DOI: 10.1109/wicom.2006.235
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Random Number Generator for Ad Hoc Sensor Network

Abstract: Network of wireless micro-sensor for monitoring physical environments has emerged as an important new application area for wireless technology. The strength of security protocols and encryption algorithms for ad hoc sensor network has been focused. Random numbers play a crucial role in them, so the quality of random number becomes one of important indexes. Because key attributes of these new types of network system are the severely constrained computation and energy resources, and an ad hoc operational environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The approach presented in (Y.H. Wang, 2006) was also tested using the NIST tests and it has been shown that some of the tests were not passed. Besides, the authors did not give the clear information about the number of sequences which were tested, what makes the two approaches hard to compare.…”
Section: Uniform Distribution Of P-valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach presented in (Y.H. Wang, 2006) was also tested using the NIST tests and it has been shown that some of the tests were not passed. Besides, the authors did not give the clear information about the number of sequences which were tested, what makes the two approaches hard to compare.…”
Section: Uniform Distribution Of P-valuesmentioning
confidence: 99%
“…In (Y.H. Wang, 2006) the authors propose a random number generator based on single-electron phenomena. It is built of a singleelectron transistor and a single-electron trap, thus, additional hardware components are needed.…”
Section: Introductionmentioning
confidence: 99%